Changes In Javanese Customary Law From The Perspectives Of Legal Sociology And Anthropology - Ghoiril Amri; Muhammad Amar Adly (AT-TAFAHUM: Journal of Law, 2023)
Javanese customary law is a dynamic value system that reflects the identity and local wisdom of the community. This article aims to analyze the meaning, original form, and transformation of Javanese customary law from the perspective of sociology and legal anthropology. The research methodology uses a qualitative approach with literature review. The results of the study indicate that Javanese customary law is flexible and able to adapt to changing times. However, significant transformations are currently occurring due to globalization, modernization, and interactions with the formal legal system. Striking changes are seen in the shift in social values related to gender equality, the repositioning of women's rights in inheritance and marriage practices, and the modernization of dispute resolution mechanisms. Sociologically, this phenomenon is a response to changes in social structure and urbanization. Anthropologically, these changes demonstrate the efforts of Javanese society to negotiate the preservation of tradition with the demands of modernity in order to maintain the relevance of collective identity in the global era.